The impact of the COVID-19 pandemic on cancer incidence, stage distribution and survival in Switzerland: a register-based cohort study - Luzius Mader; Lea Wildisen; Dominik Menges; Flurina Suter; Gautier Defossez; Jean-Luc Bulliard; Sabine Rohrmann; Katharina Staehelin (Swiss Medical Weekly)
BACKGROUND: The COVID-19 pandemic disrupted healthcare systems worldwide. This raised concerns about delays in cancer diagnosis and treatment, with potentially worse patient outcomes. The aim of this nationwide, population-based cohort study was to investigate the impact of the COVID-19 pandemic on cancer incidence, stage distribution and one-year survival in Switzerland.